2016
DOI: 10.1002/adhm.201500664
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Osteoclastogenesis/Osteoblastogenesis on Nanotopographical Titania Surfaces

Abstract: A focus of orthopedic research is to improve osteointegration and outcomes of joint replacement. Material surface topography has been shown to alter cell adhesion, proliferation, and growth. The use of nanotopographical features to promote cell adhesion and bone formation is hoped to improve osteointegration and clinical outcomes. Use of block-copolymer self-assembled nanopatterns allows nanopillars to form via templated anodization with control over height and order, which has been shown to be of cellular imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 36 publications
0
59
1
Order By: Relevance
“…We recently developed osteoblast/osteoclast progenitor co-cultures where mature phenotypes of both progenitor lines could develop on polymeric619 and metallic21 nanostructures. In this study we have used the same co-culture system on the new, hydrothermally synthesised, surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently developed osteoblast/osteoclast progenitor co-cultures where mature phenotypes of both progenitor lines could develop on polymeric619 and metallic21 nanostructures. In this study we have used the same co-culture system on the new, hydrothermally synthesised, surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we have illustrated that nanoscale topography in polymers19 and in titanium can present positive osteogenic cues while osteoclastogenesis remains unchanged; i.e. specific bioactivity has been indicated21. A more ideal i n vitro test for candidate materials would focus both on understanding osteoblast/osteoclast growth and differentiation and also would understand if surfaces are resistant to infection.…”
mentioning
confidence: 96%
“…Therefore, those nanopatterns, which are lethal to the bacteria, could possibly trigger direct or indirect mechanotransduction pathways within mammalian cells affecting their function. For instance, it has been shown that the osteogenic differentiation of MSCs is sensitive to a variety of factors including the spatial arrangement of the nanopatterns and their shapes [83,84]. Moreover, an optimum height of nanopillars could be identified yielding the highest osteogenic marker expression in MSCs [28].…”
Section: Interactions Of Mammalian Cells With the Nanopatternsmentioning
confidence: 99%
“…hydrophobicity) and surface energy, and can also further affect the absorption of proteins to the implant surface, which act as the key factor in mediating cell and bacteria activities at the tissue-implant interface. [35][36][37][38] Therefore, To further analyze these findings, additional fluorescent microscopy experiments employing SYTO ® 9/propidium iodide (to distinguish between live and dead bacteria) were carried out. Fluorescent micrographs of S. aureus ( Figure 5), E. coli (Figure 6), and MRSA ( Figure 7) cultured for 2 hours and 24 hours on Ti-TiO 2 (160°C) and Ti control samples showed that these TiO 2 coatings not only inhibited bacterial adhesion and growth but also killed the bacteria to some extent.…”
mentioning
confidence: 99%